Ammonium chloride-metal hydride based reaction cycle for vehicular applications - Stewart, Helen; Humphries, Terry; Sheppard, Drew; Tortoza, Mariana; Sofianos, M. Veronica; Liu, Shaomin; Buckley, Craig (ROYAL SOC CHEMISTRY, 2019)
© 2019 The Royal Society of Chemistry.